Utility of Neutrophil to Lymphocyte ratio and platelet to lymphocyte ratio as early predicter of severe acute biliary pancreatitis - Shah, Surendra; Paudyal, Sanjaya; Maharjan, Shanta Bir; Shah, Shailendra; Shah, Jay Narayan (Nepalese Medical Journal, 2021)
Introduction: Acute severe pancreatitis is associated with increased mortality. Several scoring systems have been used to predict severe acute pancreatitis which are either time-consuming or calculated 48 hours after admission. This study was aimed to assess the utility of neutrophils to lymphocyte ratio and platelet to lymphocyte ratio as an early predictor of severe acute biliary pancreatitis. Materials and Methods: This was a retrospective cohort study conducted from January 2017 to January 2020. Patients with non-biliary pancreatitis, referred after initial treatment, missed data, and acute pancreatitis with acute cholecystitis or cholangitis were excluded from the study. Data were collected from case sheets. Patients were divided into two groups according to the development of severe acute biliary pancreatitis based on the revised Atlanta Classification. Association of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio with severe acute biliary pancreatitis was assessed using Mann Whitney U-test. p-value < 0.05 was considered as statistically significant. Results: Total 73 cases included in the study (males/females= 0.55). Sixty-six patients (90.4%) had mild/moderate acute biliary pancreatitis, and 7 (9.6%) patients had severe acute biliary pancreatitis. There was a development of complications in 7 (9.6%) patients who had severe acute biliary pancreatitis including one mortality. The mean neutrophil to lymphocyte ratio and mean platelet to lymphocyte ratio were high in the severe acute biliary pancreatitis group compared to the nonsevere acute biliary pancreatitis group, however, these differences were not statistically significant. Conclusions: Neutrophil to lymphocyte ratio and platelet to lymphocyte ratio cannot predict severe acute biliary pancreatitis.